Teaching English to Young Learners: Professional development trainings for primary school teachers in implementing Kurikulum Merdeka - Estu Widodo; Khoiriyah Khoiriyah (ABDI: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
Kurikulum Merdeka, which is the latest educational curriculum, includes English as one of the subjects given at the elementary school level. This community service initiative was conducted in response to the challenges faced by elementary schools in implementing the Merdeka Curriculum, particularly concerning English language instruction. At SD Negeri Tunggulwulung 2, English is currently offered only once a week as an extracurricular activity, which has been deemed insufficient and ineffective in achieving the curriculum's goals. Several issues were identified through initial observations and focus group discussions with school principals and teachers, including the limited teaching techniques employed by homeroom teachers, the lack of appropriate English learning resources in classrooms, and the need to enhance the overall quality of English instruction for young learners. The objectives of this community service are addressing these issues by providing professional development training and creating a guidebook for teachers regarding teaching techniques for teaching English to young learners. The study implied a notable improvement in teachers’ knowledge of techniques for teaching English to Young Learners. Thus, after the PD series, several objectives were achieved based on the evaluation including: 1) Increased teacher competence and knowledge of English language teaching techniques appropriate for young learners, 2) Enhanced teaching confidence; many teachers reported greater confidence in planning and delivering English lessons, and the use of teaching EYL manual book, and 3) The specially developed teacher guidebook was effectively utilized as a practical reference.